RISK FACTORS AND CHARACTERISTICS OF ACTIVE AND LATENT TUBERCULOSIS IN CHILDREN ≤ 14: ACTIVE CASE FINDING: Faktor Risiko dan Karakteristik Tuberkulosis Aktif dan Laten Pada Anak ≤ 14 Tahun: Penemuan Kasus Aktif - Syahrul, Fariani; Catur Adi, Annis; Mufida Ersanti, Arina; Tri Sulistijorini, Hinu; Lipu, Yanto; Salisa, Wizara; Shafira Putri, Maurilla; Al Himny Rusydy, Muhammad; Ghanynafi, Abdullah; Fajar Nuraidah, Lutfi (Universitas Airlangga, 2025)
Background: In 2024, 135,000 tuberculosis (TB) cases were reported in Indonesian children, accounting for part of the 885,000 total TB cases nationwide. Pediatric TB remains a concern due to children’s vulnerability from immature immunity, poor nutrition, and close contact with TB patients. Early detection through active case finding (ACF) is crucial for identifying active and latent TB in at-risk populations. Purpose: To determine the prevalence of active and latent TB and analyze associated risk factors among children screened through ACF. Methods: A cross-sectional study was conducted among 870 children in Sidoarjo Regency using ACF. Active TB was diagnosed through symptom interviews and sputum examination, while latent TB was determined by tuberculin skin test (TST). Nutritional status was assessed using body mass index (BMI). Bivariate analysis was performed to assess associations with active TB. Results: The prevalence of active TB was 4%, and that of latent TB was 4.7%. Among TB cases, 46% were active and 54% latent. Malnutrition was common in active (77%) and latent (46%) TB. Bivariate analysis showed no significant associations with gender, close contact, or passive smoking. Children aged <5 years had a higher risk than those aged 5–14 years (OR = 3.11; 95% CI: 0.99–9.79; p = 0.064). Nutritional status was significantly associated with active TB (χ² = 7.85; p = 0.049). Underweight children had nearly four times higher risk of active TB compared to those with normal nutrition (OR = 3.94; 95% CI: 1.32–11.76; p = 0.018). Conclusion: ACF was effective in detecting active and latent TB among children. Malnutrition was a significant risk factor, suggesting that nutritional interventions should be integrated into pediatric TB control strategies. Patients had close contact with active TB patients.